TRAVEL GAME SEBAGAI MEDIA PEMBELAJARAN PERKALIAN DAN PEMBAGIAN - Muhtarom, Tamim (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2021)
This study aimed to determine the effectiveness of travel game media as teaching materials for multiplication and division materials for fifth grade students at SD Negeri Krejengan, Krejengan, Probolinggo District. Travel game is a learning media in the form of an educational game which is presented as a game in learning activities. The research method used is Research and Development (R&D) with a 4-D development model, namely define, design, develop, and disseminate. The research subjects were fifth grade students of SD Negeri Krejengan, Krejengan, Probolinggo District in semester 1 of the 2020/2021 academic year. The results showed that the effectiveness of the travel game media based on expert validation was in the good category. The effectiveness of the travel game media according to students at the one to one evaluation stage is also in the good category, while at the small group evaluation and field evaluation stages are in the very good category.